2020
DOI: 10.1080/19648189.2020.1762749
|View full text |Cite
|
Sign up to set email alerts
|

Properties prediction of environmentally friendly ultra-high-performance concrete using artificial neural networks

Abstract: Ultra-high-performance concrete (UHPC) results from the mixture of several constituents, leading to a highly complex material in both, fresh and hardened state. The higher number of constituents, together with a higher number of possible combinations, relative proportioning and characteristics, makes the behavior of this type of concrete more difficult to predict. The objective of the research is to build four analytical models, based on artificial neural networks (ANN), to predict the 1-day, 7-day, and 28-day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(20 citation statements)
references
References 44 publications
0
16
0
4
Order By: Relevance
“…Para aplicaciones más complejas se usan las arquitecturas de perceptrón multicapa feed-forward [2,3].…”
Section: Redes Neuronales Artificiales (Ann)unclassified
See 2 more Smart Citations
“…Para aplicaciones más complejas se usan las arquitecturas de perceptrón multicapa feed-forward [2,3].…”
Section: Redes Neuronales Artificiales (Ann)unclassified
“…En los últimos años la investigación sobre concretos especiales de alto desempeño ha sufrido un importante progreso [1][2][3]. Entre éstos cabrían destacar los concretos de ultra alto desempeño reforzados con fibras (UHPFRC por sus siglas en inglés).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…They indicated that the effect of each principal material or additive on concrete behavior can be logically evaluated by the ANN methodology. The research works of Abellán et al 32 34 have focused on combining different methods of neural networks, data mining, multi-objective optimization, and design of experiments (DOE). They studied how to improve the compressive strength over 150 MPa by using local raw materials in Colombia, while reducing the content of silica admixture.…”
Section: Introductionmentioning
confidence: 99%
“…DYNA, 88(216), pp. 38-47, January -March, 2021 reaction, combined with the use of superplasticizer to reduce the water-to-cementitious materials ratio [1][2][3]. These extremely low porosity and low permeability characteristics of ultra-high-performance concrete (UHPC) give it enhanced durability and mechanical properties over other types of concrete, such as normal concrete and high strength concrete Components and its implication in cost.…”
Section: Introductionmentioning
confidence: 99%